2011
DOI: 10.1177/147323001103900513
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Microtubules Decreases Myocardial Ischaemia-Reperfusion Injury

Abstract: Microtubules are important components of the cytoskeleton that forms the backbone of myocardial architecture, sustaining its form and size. This study investigated whether stabilizing microtubules with paclitaxel (0.1 or 1 μM) could decrease myocardial ischaemia- reperfusion injury, and reduce myocardial infarct size and the incidence of ischaemic ventricular arrhythmia. Isolated rat hearts were used, with arrhythmia induced by regional ischaemia and myocardial infarcts induced by ischaemia-reperfusion. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Furthermore, pretreatment with 1 μ m paclitaxel was shown to reduce both the infarct size after ischaemia–reperfusion and the incidence of ventricular tachycardia during ischaemia in isolated rat hearts submitted to partial occlusion of the left main coronary artery (Cao et al . ). These results were later extended to show, in the same model, an improvement in functional recovery after 15 min of regional ischaemia followed by reperfusion (Xiao et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, pretreatment with 1 μ m paclitaxel was shown to reduce both the infarct size after ischaemia–reperfusion and the incidence of ventricular tachycardia during ischaemia in isolated rat hearts submitted to partial occlusion of the left main coronary artery (Cao et al . ). These results were later extended to show, in the same model, an improvement in functional recovery after 15 min of regional ischaemia followed by reperfusion (Xiao et al .…”
Section: Discussionmentioning
confidence: 97%
“…, ; Cao et al . ), successful ligation was indicated by a >25% reduction in coronary flow, which may add variability to the results. Furthermore, we have demonstrated that treatment with paclitaxel induced, in our isolated cell model, a deleterious higher increase in cytosolic Ca 2+ levels during ischaemia and, at the highest concentration, a steep reduction during reoxygenation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Destruction of the internal architecture worsens I/R injuries and leads to apoptosis. [53], [56], [57] During ischemia, all elements of the cytoskeleton are affected, but with different kinetics. [54], [55] Moreover, the accumulation of osmotically active particles, including lactate, sodium, inorganic phosphate and creatine, induces cellular oedema.…”
Section: Structural and Functional Modificationsmentioning
confidence: 99%
“…Ischemia deconstructs the cytoskeleton. [53]- [56] The high intracellular concentrations of Ca 2+ that are associated with ischemia activate multiple phosphorylases and proteases that disassemble and degrade the cytoskeleton, thereby eliminating the functions that rely on its integrity, such as phagocytosis, exocytosis, myofilament contraction, intercellular communication and cell anchorage. Destruction of the internal architecture worsens I/R injuries and leads to apoptosis.…”
Section: Structural and Functional Modificationsmentioning
confidence: 99%